Financial Well-Being Model for Bank Employees: the Role of Financial Behavior as a Mediator - Hendro Setiawan; Rr Iramani (Universitas Hayam Wuruk Perbanas, 2023)
The aim of this study is to investigate the factors influencing the financial well-being of Bank Jatim employees in Indonesia. These factors encompass financial knowledge, financial socialization, internal locus of control, lifestyle, and current financial stress. Additionally, the study delves into the role of financial behavior as a mediator in this model of financial well-being. The respondents in this study are permanent employees of Bank Jatim, Indonesia, selected through purposive sampling. The findings reveal that financial knowledge, financial socialization, and current financial stress directly impact financial well-being. Internal locus of control affects financial well-being both directly and indirectly, mediated by financial behavior. However, financial behavior doesn't serve as a mediator for the influence of lifestyle on the financial well-being of bank employees. Furthermore, the results do not provide sufficient evidence for financial behavior mediating the effects of other determinant variables. For the company, this implies that enhancing the financial well-being of bank employees should involve efforts to augment their financial knowledge, promote financial socialization, and encourage a composed approach to managing their financial situations. As for bank employees, achieving financial well-being necessitates maintaining an internal locus of control and exhibiting prudent financial management behaviors.